Justice between fairness and love? : developing a Christian notion of justice in critical dialogue with John Rawls and Reinhold Niebuhr - Wright, Jenny Anne (Stellenbosch : Stellenbosch University, 2011)
Thesis (DTh)--Stellenbosch University, 2011.